Innovation in advanced energy: Towards a mission-oriented agenda for second-generation (2G) ethanol in Brazil - Gradin, Bernardo; Nogueira, Luiz Horta [UNESP] (Taylor & Francis, 2019)
The proportion of total primary energy supply generated from renewable sources has been increasing since the 1990s. While many have sought to incentivize the consumption of energy from renewable sources, several countries have enacted policies and programs aimed at fostering energy-related technologies and manufacturing industries as well. The task of leveraging energy resources to build an industrial base is complex. This chapter provides an overview of Brazil’s existing energy system, outlining the country’s strength in the production of several renewable energies such as wind, solar, and biofuels, and briefly commenting on aspects of technology development in this context. The chapter focuses on ethanol production, which has been an area of comparative advantage and technological strength in Brazil since the Proálcool program of the 1970s. It outlines the energy challenge facing Brazil, and argues that the country has a unique opportunity to accelerate innovation and build manufacturing capacity in second-generation ethanol (2GE), contributing to the diversification of Brazil’s energy matrix while also supporting the formation of a new technology-intensive industry. The chapter makes the case for a mission-oriented innovation agenda aimed at making Brazil a global leader in 2GE, and articulates the need for a long-term vision embodied in sound policies and a stable enabling environment.